Analytical Investigation of Cymbopogon citratus and Exploiting the Potential of Developed Silver Nanoparticle Against the Dominating Species of Pathogenic Bacteria - Basera, Priyanka; Lavania, Meeta; Agnihotri, Anil; Lal, Banwari (Frontiers in Microbiology, 2019)
Indian biodiversity is a hub for medicinal plants. Extensive research has been carried out to select plants with numerous properties which can be used for human welfare. Present research is about Cymbopogon citratus, an economically valuable medicinal plant. In this study Cymbopogon citratus was elected as a subject plant over the five selected plants (Azadirachta indica, Plumeria obtuse, Sapindus mukorossi, Capsicum annuum and Phyllanthus emblica) on the basis of antibacterial effect against dominating pathogenic species of gram positive (Bacillus cereus, Bacillus licheniformis) and gram negative (Pseudomonas aeruginosa, Escherichia coli) bacteria. Further, bioactive agents behind antibacterial potential of Cymbopogon citratus was analyzed using analytical method (Phyto-chemical, FTIR, NMR and GC-MS). Due to the broad antimicrobial spectrum, silver nanoparticles have turned into a noteworthy decision for the improvement of new medication. Therefore, this investigation further elaborated in the development of Cymbopogon citratus silver nanoparticles (CNPs). Antibacterial potential of CNPs were examine through MIC/MBC data in a range of C25- C150 (µg/ml) where, C25¬ (µg/ml) concentration of CNPs were recorded as the Minimum Inhibition concentration (MIC) and C50¬ (µg/ml) as the Minimum bactericidal concentration (MBC) with maximum diameter of zone of inhibition at C150¬ (µg/ml) concentration was observed for gram positive Bacillus cereus (20.12±0.42), Bacillus licheniformis (22.34±0.4) and gram negative Pseudomonas aeruginosa (35.23±0.46), Escherichia coli (31.87 ±0.24) bacteria. Involvement of bioactive component as a reducing and capping agent can be confirmed through FTIR spectrum of CNP. Moreover XRD, ED-XRF and SEM showed crystalline and cuboidal nature of CNPs with ~35 nm sizes. Prominently, cytotoxic analysis was conducted to understand the toxic effect of CNPs. This research highlights the potential of CNPs due to the bioactive components present in Cymbopogon citratus extract: Polyols (phenol; 1584.56±16.32 mg/L, Flavanoids) and mixture of terpenoids (Citral, Myrcene, Farnesol, β-myrcene and β –Pinene)